ANALISIS DERAJAT KESEHATAN MASYARAKAT PROVINSI BALI DENGAN MENGGUNAKAN METODE GENERALIZED STRUCTURED COMPONENT ANALYSIS (GSCA) - PURNAMA NINGSIH, PUTU NOPITA; JAYANEGARA, KETUT; KENCANA, I PUTU EKA NILA (E-Jurnal Matematika; Vol 2 No 2 (2013), 2013)
The aim of this research is to determine the relationship between environmental, behavioral, health services, education , an d economi c variables to health status in the P rovince of Bali. T hese variables are construct s (latent s ) that can not be measured directly by observation. If there was a relationship between latent and its indicators , it is recomended to use Structural Equation Modeling (SEM). In this research we used variance-based SEM i.e. Generalized Structured Component Analysis (GSCA) . This method not based on many assumptions such as the data does not have a multivariate normal distribution, the sample size does is not necessary large . Moreover , GSCA provides by overall goodness-fit of the model. The result of this research indicate s that the environmental, behavioral, economic and educational variable influenc ed health status , but health service does not significantly affect the health status; econom ic does not significantly affect the environment ; and education does not significantly affect the behavior. T he result of the FIT value ? 0. 450 and the AFIT value 0. 429 showed that overall model in this research is not good enough because of both of these value s are under 0.50.
Keywords: Latent Variable; Structural Equation Modeling (SEM); Generalized Structured Component Analysis (GSCA); Derajat Kesehatan